Wire Arc Additive Manufacturing (WAAM) Process Analysis on Stainless Steel Built Samples - Viola, Ricardo Jorge da Silva (2020)
The increasing developed complexity parts geometry demanded by the industry nowadays, represents a challenge itself, not only for the standard production processes that do not have an answer for it, but also to repair these and other parts in a more cost effectively process with a short delivery period. A technological response to these needs is relying on the Wire Arc Additive Manufacturing (WAAM) process development. This thesis was developed in Addimadour, an additive manufacturing research platform, located in Bayonne France, that has as objective the development of the Laser Metal Deposition Powder (LMD-P), Laser Metal Deposition Wire (LMD-W), Selective Laser Melting (SLM), ColdSpray – ArcSpray, Fused Deposition Modelling Robotized (FDMR) and Wire Arc Additive Manufacturing (WAAM) technologic processes, procedures, and providing consistent production parameters to industrial partners. The starting point for this thesis was an extensive research, regarding the chosen material that was a duplex stainless-steel ER2209 applied by WAAM technology. This process consists in deposing layer by layer material through an electric arc with the help of a robot that runs the paths to generate the defined geometry. Relying on an innovator process with lower process temperatures named Cold Metal Transfer (CMT) technology, different experiments were done with the aim to understand the relations between process parameters and results obtained. Firstly, three experiments were done to establish direct links between input parameters and the shape of depositions achieved. Secondly, other two experiments were done, with the aim of understand the existing dynamic between two or more cords produced together, but also to achieve the best shape possible to ensure the finishing of the surface quality. At last, two walls were produced as a result of all the knowledge collected. All the experiments done, were followed by analysis and observation of all macroscopic and microscopic specifications. Regarding the microscopic observations and measurements, it was used a microscope and software, specially designed for this type of analysis. Two different mechanical tests were done to the samples with the objective of characterize the material produced by this production process. One was the microhardness test that were carried out in all samples, using a Vickers testing machine. The results of these tests were a pattern and a range of values. For the second test, a three-point flexural test was made on samples, regarding the values of flexural force-displacement to evaluate flexural behaviour of the built samples.